Optimal capital structure model for BOT power projects in turkey. - Bakatjan, Sandalkhan
Interest in the Build/Operate?transfer (BOT) scheme for infrastructure projects has been growing rapidly, and numerous projects have been implemented around the world. Through BOT projects, a government reallocates the risks and rewards in the development of large infrastructure projects to the private sector. One key aspect to the successful implementation of the BOT concept in any country is the raising of finance by project sponsors. Financial engineering techniques and capital structuring skills are required to find the proper mix of debt and equity and to achieve successful financing for the proposed project. The objective of this paper is to present a simplified model to determine the optimum equity level for decision makers at the evaluation stage of BOT hydroelectric power plant (HEPP) project in Turkey, which takes place immediately after the completion of the feasibility study. The resulting model is the combination of a financial model and a linear programming model that incorporates an objective of maximizing the return of the project from the equity holder's point of view. To show versatility of the model, a real case study is conducted. Thus, this research is concerned with the determination of an equity funding level in BOT project finance . There are different equity levels found in BOT HEPP projects, and there is a need for such a model to determine optimal capital structure, which would assist the sponsors to ensure that the equity level necessary for optimal capital structure is available prior to the project implementation stage.
Keywords: Project management